Produkcja kancelaryjna wojewódzkiej organizacji Polskiej Zjednoczonej Partii Robotniczej w latach 1975-1990 - Magier, Dariusz (Komunizm: System - Ludzie - Dokumentacja, 2013)
The filing system of the Voivodeship-level party organisation of the Polish United Workers’ Party in the years 1975-1990 covered the operations of the filing system of the Voivodeship Committee, the provincial centres of party work (from 1982), the committees of Cities, City-Communes, and Communes, and also staff committees and the central and branch party organisations. Depending on the volume and degree of industrialisation of a region, the organisation could show even as many as a thousand staff, who participated in recording the activities of the Communist party bureaucracy. In fact, every recorded piece of information which was created as a result of the party structures’ functioning constituted a party document. The party documents consisted of internal and external records, which accumulated as a result of cases being conducted (the system of mcase files), and these comprised the whole of the documentation held moriginally in particular organisational units, whole organisations, and party organisational cells. Despite the existing rule of the reproducing of mthe work of superior party structures by the inferior units, the filing work of PUWP structures resulted in highly diverse documentation. In this marticle, the Author is going to attempt to answer three fundamental questions capturing the essence of "a party document", i.e. what were the main types of documentation produced by the Communist Party, what rules governed the formulation of the records in the party structures, and what rules governed the measures of authentication?